2007
DOI: 10.3892/or.18.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Elevated N-myristoyltransferase activity and expression in oral squamous cell carcinoma

Abstract: Abstract. N-myristoyltransferase (NMT) catalyzes the myristoylation of proteins involved in signal transduction, cellular transformation, differentiation, proliferation and oncogenesis. In this study, we report for the first time on the elevated NMT activity in oral squamous cell carcinoma (OSCC). Increased activity is marked with increased staining for NMT in the OSCC samples compared to the normal adjacent tissues. In addition, we observed increased staining for the N-myristoyltransferase inhibitor protein 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Further research will be necessary to determine the specific targets of tris DBA at cilia as well as the signaling mechanisms that regulate cilia-dependent directed migration in pancreatic cancer cells. Several studies suggest that NMT1 activity is important for the progression of different malignancies including breast cancer [31], oral squamous cell carcinoma [32], colon carcinoma [33] and gallblader cancer [34]. Our findings suggest that NMT1 is a novel therapeutic target in pancreatic cancer and warrants further investigation of tris DBA as a potential novel treatment for pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 57%
“…Further research will be necessary to determine the specific targets of tris DBA at cilia as well as the signaling mechanisms that regulate cilia-dependent directed migration in pancreatic cancer cells. Several studies suggest that NMT1 activity is important for the progression of different malignancies including breast cancer [31], oral squamous cell carcinoma [32], colon carcinoma [33] and gallblader cancer [34]. Our findings suggest that NMT1 is a novel therapeutic target in pancreatic cancer and warrants further investigation of tris DBA as a potential novel treatment for pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 57%
“…354 These results suggest that NMT might be a potential biomarker or target for colon cancer. 355 Similarly, several studies have demonstrated that NMT expression is elevated in oral squamous cell carcinoma, 356 gallbladder carcinoma, 357 and brain tumors. 235 Moreover, a cyclohexyl-octahydropyrrolo[1,2-a]pyrazine based NMT1 inhibitor, COPP-24 (Figure 17), has been shown to inhibit the proliferation of some tumor cancer cell lines.…”
Section: N-terminal Glycine Myristoylationmentioning
confidence: 97%
“…Over-expression also occurs relatively early in carcinogenesis, in colonic polyps that are not yet malignant [119]. There is also evidence for the overexpression of NMT in gallbladder and oral squamous cell carcinomas [121,122] and brain tumours [123]. Clegg and co-workers have looked at NMT in mammary epithelial cells and found that proliferative capacity correlated with NMT activity [124].…”
Section: Nmt In Cancermentioning
confidence: 99%